The Flower-Infecting Fungus Ustilaginoidea virens Subverts Plant Immunity by Secreting a Chitin-Binding Protein - Li, Guo-Bang; Fan, Jing; Wu, Jin-Long; He, Jia-Xue; Liu, Jie; Shen, Shuai; Gishkori, Zeeshan Ghulam Nabi; Hu, Xiao-Hong; Zhu, Yong; Zhou, Shi-Xin; Ji, Yun-Peng; Pu, Mei; et al. (Frontiers in Plant Science, 2021)
Ustilaginoidea virens is a biotrophic fungal pathogen specifically colonizing rice floral organ and causes false smut disease of rice. This disease has emerged as a serious problem which hinders the application of high-yield rice cultivars, by reducing grain yield and quality as well as introducing mycotoxins. However, the pathogenic mechanisms of U. virens are still enigmatic. Here we demonstrate that U. virens employs a secreted protein UvCBP1 to manipulate plant immunity. In planta expression of UvCBP1 led to compromised chitin-induced defense responses in Arabidopsis and rice, including burst of reactive oxygen species, callose deposition, and expression of defense-related genes. In vitro-purified UvCBP1 protein competes with rice chitin receptor OsCEBiP to bind to free chitin, thus impairing chitin-triggered rice immunity. Moreover, UvCBP1¬ could significantly promote infection of U. virens in rice flowers. Our results uncover a mechanism of a floral fungus suppressing plant immunity and pinpoint a universal role of chitin-battlefield during plant-fungi interactions.